Comparison of intravenous route versus nebulization of magnesium sulfate (MgSO4) for post-operative sore throat and hoarseness: A randomized comparative double-blinded clinical trial - Rashmi Raghavendra,; Surekha Kumar,; Sowmya Madihalli Janardhan Iyengar, (Asian Journal of Medical Sciences, 2022)
Background: Multiple drugs in different routes have been studied for the treatment of post-operative sore throat (POST). We are studying effect of magnesium sulfate on POST in two different routes. Aims and Objectives: This study aims to compare the efficacy of nebulization versus intravenous (IV) magnesium sulfate in reducing incidence of POST and hoarseness of voice. Materials and Methods: This prospective randomized double-blind study was done on 150 patients undergoing unilateral percutaneous nephrolithotomy (PCNL) surgeries under general anesthesia. Patients were randomly allocated into Group N (n=75) and Group I (n=75). Group N received 10 mg/kg MgSO4 in 5 mL of normal saline as nebulization 20 min before induction and 100 mL normal saline IV over 20 min post-induction. Group I received 5 mL of normal saline as nebulization pre-induction and 10 mg/kg MgSO4 in 100 mL saline IV over 20 min post-induction. Postoperatively, visual analog scale (VAS) score was used for the assessment of sore throat at rest and dynamic VAS (DyVAS) for pain during swallowing at the 0, 1st, 6th, 12th, and 24th h. Post-operative hoarseness graded on 4-point score was also assessed. Results: Incidence of POST in Group N was 29.17% compared to 52.86% in Group I at 0 h which was lower and statistically significant and results were alike at the 1st and 6th h. The VAS at rest and DyVAS were lower and statistically significant in Group N compared to Group I at the 0, 1st, and 6th h. Conclusion: Incidence of POST was significantly less with nebulized route of magnesium sulfate compared to IV route of magnesium sulfate.